Biohemijske promene u endokrinim i inflamatornim putevima nakon operacije raka dojke: laboratorijski dokazi i kliničke implikacije: Endokrino-inflamatorni biohemijski profili u raku dojke - Luo, Yafang; Xu, Jinglan; Chen, Hui (Journal of Medical Biochemistry, 2025)
Background: Breast cancer surgery induces substantial physiological stress that disrupts endocrine regulation and triggers systemic inflammation. However, the biochemical dynamics underlying these perioperative alterations remain insufficiently characterized. This study investigated laboratory-based endocrine and inflammatory biomarker changes following breast cancer surgery and explored their clinical significance. Methods: A total of 120 breast cancer patients were evaluated. Serum estradiol (E2), progesterone (P), interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-α (TNF-α) were measured preoperatively and on postoperative day 7 using validated ELISA assays with strict analytical quality control. Clinical outcomes—including psychological status, cognitive recovery, quality of life, and postoperative complications—were assessed as secondary indicators to explore potential biochemical–clinical associations. Results: Postoperative endocrine suppression was evident, with significant reductions in E2 and P levels (P < 0.05), reflecting acute stress–related modulation of hypothalamic–pituitary–gonadal (HPG) axis activity. IL-6, CRP, and TNF-α declined significantly postoperatively (all P < 0.001), demonstrating resolution of acute-phase inflammatory activation. Greater biochemical stabilization was associated with improved emotional scores, cognitive function, and quality-of-life indices, as well as a reduced incidence of postoperative complications. Conclusion: Breast cancer surgery induces characteristic biochemical changes involving endocrine suppression and systemic inflammatory activation. Monitoring hormonal and inflammatory biomarkers provides valuable insight into postoperative physiological stress, recovery mechanisms, and potential risk stratification. These findings support integrating laboratory-based biochemical assessments into postoperative management frameworks for breast cancer patients.